Coprocessamento de resíduos industriais em fornos de clínquer: uma revisão sistemática de literatura - Silva, Zilda Conceição da (Universidade Federal de São Carlos, 2021)
With the advance of industrialization, meeting the current demands of a society that is increasingly avid for consumption ends up generating serious consequences, such as the increase in wastes from industrial processes, as well as the need to dispose them. In this context it is included co-processing, which makes use of wastes as raw materials and also in energy replacement, based on the concept of energy recycling, aiming at such wastes no longer be a problem, but rather part of the solution, as in the replacement of fossil fuels. Due to the fact that such residues present potential hazards, a rigorous control of the process must be made, to assure compliance with the pre-defined safe limits. Thus, in this work, a systematic literature review was carried out, in order to identify the potential risks of industrial waste co-processing in clinker kilns. The methodology was based on using the ScienceDirect database, with specific results filters. The results obtained indicated the main potential risks: persistent organic pollutants (POPs), potentially toxic elements (old name for heavy metals), greenhouse gases (GHG) and carbon dioxide emissions. POPs can be generated more frequently with the use of industrial waste and require strict control of their effective destruction, due to their toxicity. Potentially toxic elements, due to the high potential of risk to the environment and health, must be controlled at entry and exit, so that their emissions be at levels considered acceptable. GHG and CO2 are emitted in the conventional cement manufacturing process and using co-processing, however, in co-processing, there is a reduction in the emission of these gases, by replacing conventional fuels. Furthermore, the addition of compounds from the inorganic part of the residue can or cannot interfere on some cement properties, due to the specific characteristics of these compounds, which may cause unsettling changes, depending on the residue´s composition. The surroundings of cement plants, as well as the health of workers must be routinely monitored, in order to avoid contamination of the environment and workers by compounds, which can be emitted in different ways, when co-processing takes part in the process. Thus, considering the environmental and health risks that co-processing can generate, it is pivotal to effectively control all the steps, aiming to make it as safe as possible and consolidate the main objective of this activity, which is the energy recycling for environmental benefit, with a better understanding of the potential risks of co-processing industrial waste.
Co-processing of industrial waste in clinker kilns: a systematic literature review
Keywords: Coprocessamento; Cimento; Blend; Resíduos industriais; Co-processing; Cement; Industrial waste; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL